Recent Trends in the Development of Bone Regenerative Biomaterials - Tang, Guoke; Liu, Zhiqin; Liu, Yi; Yu, Jiangming; Wang, Xing; Tan, Zhihong; Ye, Xiaojian (Frontiers in Cell and Developmental Biology, 2021)
The goal of a biomaterial is to support the bone tissue regeneration process at the defect site and eventually degrade in situ and get replaced with the newly generated bone tissue. Biomaterials that enhance bone regeneration have a wealth of potential clinical applications from the treatment of nonunion fractures to spinal fusion. The use of bone regenerative biomaterials from bioceramics and polymeric components to support bone cell and tissue growth is a longstanding area of interest. Recently, various forms of bone repair materials such as hydrogel, nanofiber scaffolds and 3D printing composite scaffolds are emerging. Current challenges include the engineering of biomaterials that can match both the mechanical and biological context of read bone tissue matrix and support the vascularization of large tissue constructs. Biomaterials with new levels of biofunctionality that attempt to recreate nanoscale topographical, biofactor and gene delivery cues from the extracellular environment are emerging as interesting candidate bone regenerative biomaterials. This review has been sculptured around a case-by-case basis of current research that is being undertaken in the field of bone regeneration engineering. We will highlight the current progress in the development of physicochemical properties and applications of bone defect repair materials and their perspectives in bone regeneration. We believe this review is intended as starting point and inspiration for future research effort to develop the next generation of bone regenerative biomaterials.